ANALYSIS OF WAITING PERIOD FOR MEN AFTER DIVORCE PERSPECTIVE OF JAMALUDDIN AṬIYAH'S MAQAṢID AS-SHARIA THEORY - Hasanuddin Hasanuddin; Muhammad Syukri Albani Nasution; Imam Yazid (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2021)
The Director General of Islamic Religious Institutional Development again issued Circular Number P-005 / DJ. III/Hk.00.7/10/2021 concerning marriage during the iddah period, according to the provisions of the circular